2016
DOI: 10.1097/ta.0000000000000947
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with bladder and urethral injuries in female children with pelvic fractures

Abstract: Prognostic/epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…As for children, the skeletally immature pelvis is more plastic and flexible because there is a more percentage of cartilage, a more porous cortical bone, and the pubic symphysis and sacroiliac joints are more elastic [ 1 ], hence the pelvic absorbs higher energy during trauma. Also, girl’s bladder neck and urethra are more vulnerable because the relative higher position in the pelvis [ 2 ], which may explain why the proportion of girls urethral injuries is higher than female adults in the current literature [ 3 ]. Although rare, the management of female pelvic fracture urethral injuries is complex and there is no guideline yet.…”
Section: Discussionmentioning
confidence: 99%
“…As for children, the skeletally immature pelvis is more plastic and flexible because there is a more percentage of cartilage, a more porous cortical bone, and the pubic symphysis and sacroiliac joints are more elastic [ 1 ], hence the pelvic absorbs higher energy during trauma. Also, girl’s bladder neck and urethra are more vulnerable because the relative higher position in the pelvis [ 2 ], which may explain why the proportion of girls urethral injuries is higher than female adults in the current literature [ 3 ]. Although rare, the management of female pelvic fracture urethral injuries is complex and there is no guideline yet.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have noted that initial emergency department assessment can miss this diagnosis in as many as 40% of cases . A recent study from the National Trauma Data Bank found that in girls, urethral injury appears to be most common in the presence of a vaginal laceration, pelvic circle disruption, multiple pelvic fractures or sacral spine injury . Any girl or woman with this combination of injuries should be closely evaluated for urethral injury.…”
Section: Discussionmentioning
confidence: 99%
“…Delay in identification, diagnosis and appropriate management can lead to increased morbidity for these patients, resulting in complications such as urethral stricture and infection [6]. Other documented complications include pelvic abscess/sepsis, urethrocutaneous fistulae, severe pelvic inflammation, septic shock, peritonitis, necrotising fasciitis, as well as bladder entrapment [6,17,18] Early detection and management of bladder and urethral injuries is thus a vital part in the care of the trauma patient. Unfortunately due to the nature of these presentations this is not always achievable due to prioritisation of life-threatening injuries.…”
Section: Discussionmentioning
confidence: 99%